Draw 50 sharks, whales, and other sea creatures - Ames, Lee J.; Budd, Warren (New York : Doubleday, 1989)
Provides step-by-step instructions for drawing a variety of sharks, whales, and other sea creatures, including the hammerhead shark, humpback whale, and giant sea turtle.
Keywords: Sharks in art -- Juvenile literature; Whales in art -- Juvenile literature; Marine fauna in art -- Juvenile literature; Drawing -- Technique -- Juvenile literature; Sharks in art; Whales in art; Marine animals in art; Drawing -- Technique; Sharks in art; Whales in art; Marine animals in art; Drawing -- Technique; Marine fauna in art; Sharks in art; Whales in art; Marine animals in art; Drawing -- Technique